Phytochemical composition, mosquito larvicidal, ovicidal and repellent activity of Calotropis procera against Culex tritaeniorhynchus and Culex gelidus - Gaurav Kumar; Loganathan Karthik; Bhaskara Rao Kokati Venkata; Arivarasan Vishnu Kirthi; Chidambaram Jayaseelan; Abdul Abdul Rahuman (Bangladesh Pharmacological Society, 2012)
Focus of this study was to determine the phytochemical composition and mosquito controlling potential of aqueous extract of Calotropis procera (Ait.) R.Br. leaves using in vitro methods. Preliminary phytochemical analysis of the extract showed the presence of phenolic compounds, flavonoids, alkaloids, tannins, saponins, glycosides and phytosterols as major phytochemical groups. Aqueous extract of C. procera leaves (1,000 ppm) exhibited 100% larvicidal activity against fourth instar larvae of Culex tritaeniorhynchus and Cx. gelidus. Extract treatment (1,000 ppm) of both mosquitoes eggs resulted in to 100% ovicidal activity. At 1,000 ppm, extract provided complete protection from mosquito bite for 240 min against both mosquitoes; however at lower doses the protection time was less. The findings of the current study emphasise the potentiality of C. procera leaves for controlling the mosquito population and their possible way in the developing the natural insecticide for the control of Cx. tritaeniorhynchus and Cx. gelidus mosquitoes.